Modelling zakat as tax deduction: A comparison study in Indonesia and Malaysia - Provita Wijayanti; Farikha Amilahaq; Osmad Muthaher; Nurul Syuhada Baharuddin; Nur Raihana Mohd Sallem (Journal of Islamic Accounting and Finance Research, 2022)
Purpose - This study aims to analyze the differences in compliance and implementation of paying zakat and taxes with zakat regulatory antecedents such as tax deduction.Method - 129 respondents from academicians and managers in Indonesia and Malaysia were taken by convenience sampling method and analyzed using the Mann-Whitney test and linear regression.Result - The result shows that there are differences in zakat payment compliance between Indonesia and Malaysia. The implementation of zakat as tax deduction regulation has a significant effect on zakat and tax compliance behavior in both countries. Meanwhile, zakat as a tax deduction regulation executed in Malaysia makes tax compliance behavior higher than in Indonesia.Implication - Socialization from both the tax officials and zakat officials that zakat can be used to reduce taxable income is needed. It is suggested to apply zakat as a tax deduction for Indonesia as well as Malaysia.Originality - This research contributes to the Indonesian government in exploring the potential of Indonesian Muslims in paying zakat and taxes.